Discovery of Small Molecules that Induce the Degradation of Huntingtin. (9th August 2017) - Tomoshige, Shusuke; Nomura, Sayaka; Ohgane, Kenji; Hashimoto, Yuichi; Ishikawa, Minoru
Abstract: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by the aggregation of mutant huntingtin (mHtt), and removal of toxic mHtt is expected to be an effective therapeutic approach. We designed two small hybrid molecules (1 and2 ) by linking a ligand for ubiquitin ligase (cellular inhibitor of apoptosis protein 1; cIAP1) with probes for mHtt aggregates, anticipating that these compounds would recruit cIAP1 to mHtt and induce selective degradation by the ubiquitin‐proteasome system. The synthesized compounds reduced mHtt levels in HD patient fibroblasts and appear to be promising candidates for the development of a treatment for HD.